Hubungan Antara Motivasi Belajar dan Prestasi Akademik Dalam Mata Pelajaran IPA di Sekolah Dasar - Dhea Ramadhani; Ari Suriani; Sahrun Nisa (Pusat Riset dan Inovasi Nasional, 2024)
Learning motivation has a strong relationship with academic achievement in science subjects in elementary schools. Learning motivation refers to the drive that comes from within the students or from their surrounding environment that encourages them to learn. This study employs a literature review method to examine the relationship between learning motivation and students' academic achievement in science subjects in elementary schools. The results show that high learning motivation will encourage students to be more diligent, persistent, and enthusiastic in learning science. Active involvement in the learning process, ability to manage study time, and perseverance in completing science assignments will positively impact the attainment of optimal academic achievement in science subjects in elementary schools.